Customer involvement in product development: Using Voice of the Customer for innovation and marketing. Issue 1 (27th September 2019) - Melander, Lisa
Abstract : Purpose: Being innovative and bringing new products to the market fast is important for firms to stay competitive. Customers are important for providing input to product developments in industrial markets. The purpose of this paper is to increase understanding of how firms use Voice of the Customer (VoC) in product development and how VoC can complement other customer involvement methods. Design/methodology/approach: The paper is based on a qualitative case study of a global leading and innovative firm, a maker of tools for the automotive industry. The study provides detailed insight into the implementation of VoC for product development. Findings: The process of customer involvement in product development through VoC is explored. The study shows that by using the VoC method, firms can gather knowledge for input to product development projects while developing relationships with a larger number of customers. The findings point out that VoC can be modified to focus on customer needs related to product development as well as marketing efforts requiring cross-functional collaboration. The VoC method is suitable for combining with other customer involvement methods such as project involvement and pilot testing. Through VoC, firms have the chance to benchmark across industries and regions. Research limitations/implications: The paper provides insights into the VoC process of customer involvement aimed at product development. The case study provides an illustration of how an industrial firm uses VoC in product development. The paper points out the importance of managing external (customer) involvement in product development and internal (cross-functional) collaborations. Practical implications: A set of questions that firms can ask themselves before embarking on customer involvement has been developed. The paper shows that customers can be involved at a number of points in time, have a wide range of roles and contribute different knowledge. VoC is suitable for combining with other customer involvement methods. Originality/value: The contribution of the paper consists of a case study illustrating how customer involvement in product development can be achieved through VoC. A number of customer involvement methods for product development are discussed for combining with VoC, showing how different methods are complementary in product development.